(untitled) (Eurasian Research Bulletin, 2023)
As the abstract suggests, this topic is focused on the issues related to taxation of small and medium-sized businesses and ways to improve this practice. Taxation is a crucial aspect of any business operation, and small and medium-sized enterprises (SMEs) are no exception. In most countries, SMEs form the backbone of the economy, and their contribution to the national GDP cannot be overstated. However, SMEs often face a variety of challenges in complying with tax regulations, including lack of awareness, inadequate resources, and complex tax rules. Therefore, it is essential to address these issues and develop effective measures to improve the taxation practice for SMEs. This abstract serves as an introduction to the discussion of the key aspects related to taxation of SMEs and ways to enhance the compliance and efficiency of the tax system for these businesses..